A Computer‐Aided Model for the Simulation of Railway Ballast by Random Sequential Adsorption Process. (29th December 2017) - Benedetto, Andrea; Bianchini Ciampoli, Luca; Brancadoro, Maria Giulia; Alani, Amir M.; Tosti, Fabio
Abstract: This article presents a computer‐aided multistage methodology for the simulation of railway ballasts using the Random Sequential Adsorption (RSA – 2D domain) paradigm. The primary stage in this endeavor is the numerical generation of a synthetic sample by a "particle sizing and positioning" process followed by a "compaction" process. The synthetic samples of ballast are then visualized in the Computer‐Aided Design (CAD) environment. The outcomes of the simulation are analyzed by comparison with the results of an experimental investigation carried out using a methacrylate container in which real samples of railway ballast are formed. A test of model reliability is carried out between the aggregates number and the grading curves of the synthetic sample and the real one. A validation is therefore performed using the ground‐penetrating radar (GPR) nondestructive testing (NDT) method and the finite‐difference time‐domain (FDTD) simulation developed in a computer‐aided environment. The results prove the viability and the applicability of the proposed modeling for the assessment of railway ballast conditions.